ADMINISTRATION OF CACAO BEANS (Theobroma cacao L.) EXTRACTS DECREASE MALONDIALDEHYDE CONCENTRATION AND INCREASE BLOOD NOx CONCENTRATION IN WHITE RAT (Ra"us norvegicus) INDUCED BY PSYCHOSOCIAL STRESS - IA, Dewi Wiryanthini; IGM, Aman; NA, Bagiada (Medicina, 2012)
Increased production of reactive oxygen species (ROS) causing accumulation of oxidative damage caused by exceeding anti oxidant capacity in the body. Psychological stress as psychosocial stress can induce oxidative stress which subsequently cause increase blood malondialdehyde (MDA) and decrease blood nitrate and nitrite (NOx) concentration as intermediate product of nitric oxide (NO). Cacao beans extracts contained anti oxidant flavanols consist of catechin, epicatechin and procyanidin. The aims of this study is to investigate the effect of cacao beans (Theobroma cacao L.) extracts for decreasing MDA and increasing NOx concentration in white rat (Ra$us norvegicus) blood in stress oxidative state induced by psychosocial stress. It is an experimental study with Pretest-Postest Control Group Design. This study revealed decrease MDA concentration in group P1 (11.47 vs 8.04), P2 (11.92 vs 5.44) and P3 (11.69 vs 2.87) with P = 0.000 and increase NOx concentration in oxidative stress white rat induced by psychosocial stress a[er administration of cacao beans extract in group P1 (1909.83 vs 2085.16), P2 (1912.5 vs 2231.83) and P3 (1871.5 vs 2339.83) with P = 0.005. This study showed that cacao beans extract can inhibit oxidative stress caused by psychosocial stress.